Dialog and evangelization according to Charles de Foucauld and The Implication for the Church of Indonesia - Materius Kristiyanto (Journal of Asian Orientation in Theology, 2022)
This qualitative research uses a literature review method with the aim of exploring Charles de Foucauld's thoughts on dialogue and evangelization among Muslims. The ideas of dialogue and evangelization can be traced from his life story as a Catholic priest and missionary.  His spiritual life was colored by seeking the last place, as Jesus lived in Nazareth, in several Trappist monasteries, and finally chose to become a missionary priest. He became a missionary in Algeria in preparation for a mission to Morocco. He lived among the Muslims in Beni Abbs - Tuaregh and Tamanrasset. He built a house of brotherhood to build brotherhood with everyone. He testifies to a simple and ascetic life. After Foucauld's death, several groups of followers grew in Europe, namely Piccoli Fratelli and Piccole Sorelle. They form small communities that continue the spirit of dialogue and evangelization by living as a unit in society in the form of an inclusive basic community. The basic community aims to build universal brotherhood, regardless of ethnicity, religion, and race. The inclusive dialogue model is very relevant for the multicultural and multireligious Indonesian society.